1999
DOI: 10.1136/bmj.318.7197.1527
|View full text |Cite
|
Sign up to set email alerts
|

Influence of data display formats on physician investigators' decisions to stop clinical trials: prospective trial with repeated measures

Abstract: Objective To examine the effect of the method of data display on physician investigators' decisions to stop hypothetical clinical trials for an unplanned statistical analysis. Design Prospective, mixed model design with variables between subjects and within subjects (repeated measures). Setting Comprehensive cancer centre. Participants 34 physicians, stratified by academic rank, who were conducting clinical trials. Interventions Participants were shown tables, pie charts, bar graphs, and icon displays containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 13 publications
4
94
0
2
Order By: Relevance
“…The way in which information is presented to individuals may also affect the decisions they make [23,24]. Nine of the eleven studies in this review presented information to clinicians using color coding based on a 'traffic light' alerting system, where red indicates a measure that requires action and green indicates that at present the indicator is 'normal' or that no action needs to be taken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The way in which information is presented to individuals may also affect the decisions they make [23,24]. Nine of the eleven studies in this review presented information to clinicians using color coding based on a 'traffic light' alerting system, where red indicates a measure that requires action and green indicates that at present the indicator is 'normal' or that no action needs to be taken.…”
Section: Discussionmentioning
confidence: 99%
“…has been shown to impact on the accuracy of decisions taken by clinicians [24] . At a time when health care organizations are being encouraged to introduce dashboards in order to improve quality of care and patient safety, it is important to review the effect of quality and clinical dashboards on care processes and patient outcomes and to understand how variations in the design of dashboards impact their effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study by Elting et al [14] compared visualization formats for communicating clinical trial risk. In clinical trials, a significant difference in error can often mean a number of lives lost (or saved).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we follow Cleveland and McGill's experiments which compare user accuracy with various position-length chart types (see Figure 1). We also extend their work by building on both recent crowdsourced graphical perception studies [16,20] and affective priming studies [14,27] to examine how emotion influences visual judgment [23].…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to odd descriptions of the data, such as, "The more male a person is, the taller he/she is." More seriously, Elting et al [5] found significant differences in the number of errors produced by physicians viewing the same clinical study data in several charts of different types and presentation styles. The design of data presentation in this case affects not only users' immediate perceptions, but also the decisions they make.…”
Section: Introductionmentioning
confidence: 99%